Linear Stability of Magneto Viscoelastic Walter’s B′ Type with Heat and Mass Transfer - D. M. Mostafa (Advances in High Energy Physics)
In this paper, the couple influence of axial magnetic field and the heat and mass transfer on two rotating cylinders of Walter’s B′ viscoelastic fluids by using the potential flow theory of viscoelastic fluid has been investigated. The normal mode method is used to compute the growth rate of disturbance. The influence of gravity is ignored at the interface, while the effect of surface tension is present in the analysis. The effect of the parameters on the stability is studied. It is found that the rotation of the inner cylinder induces stability. Furthermore, the viscoelastic ratio of fluids has a stabilizing influence. The heat and mass transfer, magnetic permeability ratio, and Ohnesorge number have a stabilized influence, while viscosity ratio of fluids, density ratio of fluids, and axial magnetic field have destabilizing influence on the considered system.